Macintosh's System 7.6--Mac's Latest System Software - DESIDOC, Director (DESIDOC Journal of Library & Information Technology, 2002)
One of the benefits of Desktop Publishing (DTP) is that it 'offers potentially enhanced presentation of information as a low cost alternative to traditional typesetting. Given this opportunity presented by DTP, it could" be utilised by information services for three reasons, viz., (i) to reduce the production costs; (ii) to enhance' the quality of publications; and (iii) to make it feasible to produce quality publications that could not be afforded by traditional techniques. http://dx.doi.org/10.14429/dbit.12.1.3051